The need for research on record keeping metadata standardization of electronic health records system integration / Seri Intan Idayu Shahrul Asari, Nurussobah Hussin and Ahmad Zam Hariro Samsudin. - Shahrul Asari, Seri Intan Idayu; Hussin, Nurussobah; Samsudin, Ahmad Zam Hariro (Universiti Teknologi MARA Cawangan Selangor, 2017)
The implemented system still has limited integration and interoperability for supporting clinical operations among other Ministry of Health Malaysia (MOHM) hospitals, health centres, and clinics. The adoption of EHR system is happening very slowly to become fully integrated in both primary care and within hospital settings. Therefore, the objectives of this paper are to discuss about the challenges in EHR integration and the consideration towards metadata standardization. It is also to analyse the current status of such research topics in it relevancy, the dominant countries involve and the subject areas that contributed the most. Method being used in this is paper is literature review analysis and Scopus analyse tools. This papers begin with the explanation of general metadata that is required in system integration. Then the discussion highlighted the importance of metadata in electronic document management. Furthermore, the discussion reveals the challenges or barriers includes interoperability, security and privacy and preservation regarding electronic health records system integration. The important part of this paper is the analysis of related research. It is important in recognizing the relevancy of research topic and the area that has been explored by previous researchers. The findings conclude that the topics is demanded to be explore further and there is more to reveals especially in the management areas.